2014
DOI: 10.7555/jbr.27.20130072
|View full text |Cite
|
Sign up to set email alerts
|

Schistosoma japonicum infection induces macrophage polarization

Abstract: The role of macrophages (Mφ) as the first line of host defense is well accepted. These cells play a central role in orchestrating crucial functions during schistosomal infection. Thus, understanding the functional diversity of these cells in the process of infection as well as the mechanisms underlying these events is crucial for developing disease control strategies. In this study, we adopted a Mφ polarization recognition system. M1 macrophage was characterized by expressing CD16/32, IL-12 and iNOS. M2 macrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 30 publications
2
24
0
Order By: Relevance
“…In S. japonicum -infected mice, a T helper (Th)1 response is initiated early in infection followed by an interleukin (IL) 4 and IL-13-mediated dominant Th2 immune response as eggs become lodged in the host liver. At this time macrophages in the egg-induced granuloma are polarized into a M2 macrophage phenotype 7 8 . These macrophages, known as alternatively activated macrophages (AAM), contribute to the development of fibrosis, maintenance of granuloma, tissue repair, and host survival 9 10 .…”
mentioning
confidence: 99%
“…In S. japonicum -infected mice, a T helper (Th)1 response is initiated early in infection followed by an interleukin (IL) 4 and IL-13-mediated dominant Th2 immune response as eggs become lodged in the host liver. At this time macrophages in the egg-induced granuloma are polarized into a M2 macrophage phenotype 7 8 . These macrophages, known as alternatively activated macrophages (AAM), contribute to the development of fibrosis, maintenance of granuloma, tissue repair, and host survival 9 10 .…”
mentioning
confidence: 99%
“…Previous studies have identified alternative activated macrophages as a hallmark of various parasitic diseases, including filarial nematode Brugia malayi [ 10 ], Nippostrongylus brasiliensis [ 11 ], Trichinella spiralis [ 12 ], Schistosoma japonicum [ 13 ], and Heligmosomoides polygyrus [ 14 ], along with high expression of Chi3l3 and major eosinophilic infiltration. The brain inflammation of AC-infected mice was characterized by major infiltration of eosinophils and “inflammatory” macrophages (Ly-6C + CCR2 + CX3CR1 lo ) and a sharp increase in brain Chi3l3, an eosinophilic chemotactic factor also known as Chi3l3, ECF-L or Ym1.…”
Section: Discussionmentioning
confidence: 99%
“…Although AC may produce severe neurological disease, little is known about its underlying pathogenic mechanisms. It is widely assumed that type 2 immunity, a major protective mechanism against helminth infection, such as filarial nematode Brugia malayi [ 10 ], Nippostrongylus brasiliensis [ 11 ], Trichinella spiralis [ 12 ], Schistosoma japonicum [ 13 ], and Heligmosomoides polygyrus [ 14 ], is involved in the process of helminth infection. And IL-5 [ 15 , 16 ], IL-13 [ 17 ], and Eotaxin [ 18 , 19 ] are currently regarded as the common characteristics in eosinophilic infiltration-related diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The granulomatous immune response is also characterized by complicated cells, such as macrophages, which account for approximately 30% of granuloma cells [ 48 , 49 ]. A previous study showed that IFN-γ, the product of Th1 cells and acting predominantly on macrophages to drive M1 differentiation, which secret various pro-inflammatory cytokines, such as TNF-α, IL-6 and IL-12, and activate the adaptive immune response [ 50 ]. High levels of IL-4 and IL-13, which can be secreted primarily by type-2 immune cells such as Th2 cells to act toward the alternative activation of macrophages into the M2 phenotype [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that IFN-γ, the product of Th1 cells and acting predominantly on macrophages to drive M1 differentiation, which secret various pro-inflammatory cytokines, such as TNF-α, IL-6 and IL-12, and activate the adaptive immune response [ 50 ]. High levels of IL-4 and IL-13, which can be secreted primarily by type-2 immune cells such as Th2 cells to act toward the alternative activation of macrophages into the M2 phenotype [ 50 , 51 ]. Our in vitro study suggested that the increased M2 macrophages polarization induced by fucoidan was probably due to the enhanced Th2 cells, while the declined M1 macrophages related to the decreased Th1 cells.…”
Section: Discussionmentioning
confidence: 99%